`How Now Brown Cow?': Mordant reflections on English examination results for Guyana - Cox, David
This paper discusses the results of research conducted on the English language and English literature Caribbean Examinations Council (CXC) and General Certificate of Education (GCE) A'Level examination results in Guyana between 1960-1984. It suggests that the level of failure adversely affects the entire spectrum of the social and economic development of young people--employment opportunities, motivation, mobility, cultural activities, and creativity. It recommends that more attention be paid to teacher training, teaching methods, and secondary education in general
Keywords: Examination results